Automatic detection and classification of coastal Mediterranean fish from underwater images: Good practices for robust training - Catalán, Ignacio A.; Álvarez-Ellacuría, Amaya; Lisani, José-Luis; Sánchez, Josep; Vizoso, Guillermo; Heinrichs-Maquilón, Antoni Enric; Hinz, Hilmar; Alós, Josep; Signarioli, Marco; Aguzzi, Jacopo; Francescangeli, Marco; Palmer, Miquel (Frontiers in Marine Science, 2023)
Further investigation is needed to improve the identification and classification of fish in underwater images using artificial intelligence, specifically deep learning. Questions that need to be explored include the importance of using diverse backgrounds, the effect of (not) labeling small fish on precision, the number of images needed for successful classification, and whether they should be randomly selected. To address these questions, a new labeled dataset was created with over 18,400 recorded Mediterranean fish from 20 species from over 1,600 underwater images with different backgrounds. Two state-of-the-art object detectors/classifiers, YOLOv5m and Faster RCNN, were compared for the detection of the 'fish' category in different datasets. YOLOv5m performed better and was thus selected for classifying an increasing number of species in six combinations of labeled datasets varying in background types, balanced or unbalanced number of fishes per background, number of labeled fish, and quality of labeling. Results showed that i) it is cost-efficient to work with a reduced labeled set (a few hundred labeled objects per category) if images are carefully selected, ii) the usefulness of the trained model for classifying unseen datasets improves with the use of different backgrounds in the training dataset, and iii) avoiding training with low-quality labels (e.g., small relative size or incomplete silhouettes) yields better classification metrics. These results and dataset will help select and label images in the most effective way to improve the use of deep learning in studying underwater organisms.